Experimental Protoporphyria: Effect of bile acids on liver damage induced by griseofulvin - Martinez, Maria del Carmen (2015)
The effect of bile acids administration to an experimental mice model of Protoporphyria produced by griseofulvin (Gris) was investigated. The aim was to assess whether porphyrin excretion could be accelerated by bile acids treatment in an attempt to diminish liver damage induced by Gris. Liver damage markers, heme metabolism, and oxidative stress parameters were analyzed in mice treated with Gris and deoxycholic (DXA), dehydrocholic (DHA), chenodeoxycholic, or ursodeoxycholic (URSO). The administration of Gris alone increased the activities of glutathione reductase (GRed), superoxide dismutase (SOD), alkaline phosphatase (AP), gamma glutamyl transpeptidase (GGT), and glutathione-S-transferase (GST), as well as total porphyrins, glutathione (GSH), and cytochrome P450 (CYP) levels in liver. Among the bile acids studied, DXA and DHA increased PROTO IX excretion, DXA also abolished the action of Gris, reducing lipid peroxidation and hepatic GSH and CYP levels, and the activities of GGT, AP, SOD, and GST returned to control values. However, porphyrin accumulation was not prevented by URSO; instead this bile acid reduced ALA-S and the antioxidant defense enzymes system activities. In conclusion, we postulate that DXA acid would be more effective to prevent liver damage induced by Gris.